2022
DOI: 10.3390/ijerph19095623
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tobacco and Nicotine Products among Young People in Denmark—Status in Single and Dual Use

Abstract: Lots of new tobacco or nicotine products are being launched, e.g., e-cigarettes and smokeless tobacco, which appeal especially to the youngest part of the population. For example, the use of smokeless tobacco among Danish youth rose from approx. 2% in 2010 to 9% in 2020. Hence, there is an urgent need to follow and intervene against youth tobacco or nicotine product use. This study explored the current use of cigarettes, e-cigarettes, heated tobacco, and smokeless tobacco among Danish 15- to 29-year-olds. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Because ours was the first Swiss study to detail use prevalence of most available tobacco and nicotine products among 15-21-year-olds, we can only speculate about use trends. Our results align with earlier studies from Switzerland, Germany, and Denmark that found adolescents were more likely to smoke tobacco cigarettes than use any other products (13)(14)(15)(16)(17). While the 2017 Swiss National Health Survey (SNHS) found 10.7% of Swiss youth smoked daily, we found smoking prevalence was higher (14.2%).…”
Section: Discussion Tobacco and Nicotine Productssupporting
confidence: 91%
See 4 more Smart Citations
“…Because ours was the first Swiss study to detail use prevalence of most available tobacco and nicotine products among 15-21-year-olds, we can only speculate about use trends. Our results align with earlier studies from Switzerland, Germany, and Denmark that found adolescents were more likely to smoke tobacco cigarettes than use any other products (13)(14)(15)(16)(17). While the 2017 Swiss National Health Survey (SNHS) found 10.7% of Swiss youth smoked daily, we found smoking prevalence was higher (14.2%).…”
Section: Discussion Tobacco and Nicotine Productssupporting
confidence: 91%
“…Like other studies, we found use of tobacco burning products increases with age ( 13 , 14 , 23 ). Neurobiological studies indicate that younger people are more quickly addicted to substances ( 24 ), and in Switzerland youth may legally smoke tobacco at 16, while in most other countries the legal smoking age is 18 ( 25 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations